Community structure of bivalves in the waters of Terkulai Island Tanjungpinang City - Dilla Sahilla; Susiana Susiana; Dedy Kurniawan; Rochmady Rochmady; Karyawati Karyawati (Agrikan: Jurnal Agribisnis Perikanan, 2023)
Bivalves are marine biota found in the waters of Terkulai Island, Tanjungpinang City, and as one of the catches of fishermen.Â  However, there is no research study on bivalves. The purpose of this study was to determine the types of bivalves, the structure of the bivalve community, and the relationship between the structure of the bivalve community and environmental parameters in the waters of Terkulai Island. This research was conducted in April-August 2023. Determination of sampling points using random sampling method as many as 30 points with sampling plots measuring 1x1m. bivalves found in the type of sand substrate slightly muddy gravel as many as 10 species, and the gravel sand substrate type consists of 2 species. The Circe scripta species was the species with the highest density in both substrate types with values of 0.37 ind/m2 and 0.20 ind/m2. The community structure based on the substrate type of slightly silty gravel and gravelly sand was obtained for the diversity value (H') of the bivalves ranging from 1.804 and 0.562. The uniformity value (E) ranged from 0.784 to 0.244. the dominance value (D) was found to range from 0.253 and 0.625. The measurement results of the physicochemical parameters of the waters are still at a feasible threshold for bivalve life. The principal component analysis (PCA) shows the density of bivalves with water parameters has a positive correlation with DO and pH.